Exploring Korean College of Education Pre-service Teacher Persistence Toward a Teaching Career: Quantitative Analysis of Reasons and Factors for Persisting - Yvette Denise Murdoch; Hyejung Lim (SAGE Open, 2022)
Teacher attrition is a global concern. Because motivation drives a teacher to persist in their teaching career and affects their effectiveness, persistence among pre-service teachers is important. This exploratory study ( N  = 55) of college of education students at a university in metropolitan Seoul, South Korea, using survey data, used (a) independent samples t-test to determine reasons for persisting and (b) correlation analysis among demographics and five persistence factors: Academic Integration, Social Integration, Supportive Service Satisfaction, Degree Commitment, and Academic Conscientiousness to understand persistence to a teaching career. The main motivation, job security, moderately correlated with two persistence factors while general interest in the subject and English proficiency positively associated with all persistence factors. The higher students assessed their English proficiency, the more they did not wish to become a teacher because of “salary.” More frequent and earlier teaching practicums and capitalizing on the Halo Effect are discussed for positive results.